Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kualitas Pelayanan Pada Dinas Pertanian Dan Ketahanan Pangan Kabupaten Wajo - Andi Anugrah Aco; Eva Agustiani; Mulyadi Mulyadi (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This research was motivated by the fact that the quality of services provided at the Wajo Regency Agriculture and Food Security Service was not yet optimal, as there were still several employees who lacked the technical skills to carry it out. The aim of this research is to determine the influence of Human Resource Competency on Service Quality at the Wajo Regency Agriculture and Food Security Service. The population in this research is the community receiving services from the Wajo Regency Agriculture and Food Security Service during the last 2 months, totaling 28 people, all of whom were used as respondents with saturated engineering samples. Data collection was carried out using questionnaires and documentation studies. Meanwhile, the data analysis techniques used are quantitative descriptive analysis techniques and associative analysis techniques. The results of the research show that: Human Resource Competency has a strong influence on Service Quality at the Wajo Regency Agriculture and Food Security Service. It is recommended that the leadership at the Agriculture and Food Security Service of Wajo Regency should strive to improve the quality of their services to the community, namely by increasing the competency of human resources, in this case the employees who work there, along with other factors that influence the quality of service in their organization. .